Clinical Outcomes of Rapid Versus Gradual Blood Pressure Normalisation in Asymptomatic Hypertensive Urgency: A Systematic Review and Meta-Analysis - Abdullah; Rahyuni Devilia Nofa; Maimun Syukri; Desi Salwani (Archives of The Medicine and Case Reports, 2026)
Hypertensive urgency presents a clinical dilemma regarding optimal blood pressure management. Whilst guidelines advocate gradual reduction to prevent organ damage through vascular autoregulation disruption, rapid normalisation remains common in clinical practice. This systematic review and meta-analysis synthesised evidence comparing rapid and gradual blood pressure normalisation strategies in asymptomatic hypertensive urgency. Systematic searches of Scopus, PubMed/MEDLINE, and Embase were conducted. Nine randomised or quasi-randomised controlled trials were included involving 4,195 adult participants with asymptomatic hypertensive urgency. Studies compared rapid blood pressure normalisation with gradual reduction over various timeframes. Primary outcomes included acute kidney injury (AKI), symptomatic hypotension, and major adverse cardiovascular events (MACE). Random-effects meta-analysis using standardised mean difference (Hedges' g) was performed. Rapid blood pressure normalisation was associated with significantly higher adverse events compared with gradual reduction (pooled SMD = 0.8854, 95% confidence interval [0.6235–1.1472], p < 0.000001; I² = 61.11%). Subgroup analysis revealed substantial effects for AKI (SMD = 0.9199, p = 0.000012) and symptomatic hypotension (SMD = 1.0103, p < 0.001), whilst MACE showed no significant difference (SMD = 0.3777, p = 0.435). Heterogeneity was moderate to substantial (I² = 61.11%, Tau² = 0.0881). Sensitivity analyses demonstrated robust findings. In conclusion, gradual blood pressure reduction in asymptomatic hypertensive urgency was superior to rapid normalisation, particularly for preventing acute kidney injury and symptomatic hypotension. These findings support current guideline recommendations for cautious, titrated antihypertensive strategies in this population.